2022
DOI: 10.3390/md20020131
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal and Immunostimulating Activities of Monogalactosyl Diacylglyceride from Coccomyxa sp. KJ, a Green Microalga, against Murine Norovirus and Feline Calicivirus

Abstract: Human noroviruses are the most common pathogens causing acute gastroenteritis and may lead to more severe illnesses among immunosuppressed people, including elderly and organ transplant recipients. To date, there are no safe and effective vaccines or antiviral agents for norovirus infections. In the present study, we aimed to demonstrate the antiviral activity of monogalactosyl diacylglyceride (MGDG) isolated from a microalga, Coccomyxa sp. KJ, against murine norovirus (MNV) and feline calicivirus (FCV), the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We recently reported that MGDG, a component of Coccomyxa sp. KJ, exerts virucidal effects against herpes simplex virus type 2, SARS-CoV-2, murine norovirus, and feline calicivirus [10][11][12]. As shown in Figure 6, 1 mg/day of MGDG exerted therapeutic effects in IFV-infected mice.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We recently reported that MGDG, a component of Coccomyxa sp. KJ, exerts virucidal effects against herpes simplex virus type 2, SARS-CoV-2, murine norovirus, and feline calicivirus [10][11][12]. As shown in Figure 6, 1 mg/day of MGDG exerted therapeutic effects in IFV-infected mice.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, we investigated its antiviral component(s) using a bioactivity-guided assay. Among these components, monogalactosyl diacylglyceride (MGDG) exerted virucidal effects against herpes simplex virus type 2, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and norovirus [10][11][12]. In vivo studies of norovirus have shown that MGDG suppresses viral replication and induces the production of virus-specific antibodies [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiviral activity was estimated using selectivity indices (SIs), calculated as the ratio of 50% cytotoxic concentration (CC 50 ) to 50% effective concentration (EC 50 ) (SI = CC 50 /EC 50 ) [27]. To evaluate the cytotoxicity of GSE in Vero, MDCK, HeLa, and RAW 264.7 cells, uninfected subconfluent cells were cultured at 37 • C in a CO 2 incubator in the presence of increasing concentrations of GSE.…”
Section: Antiviral Assaymentioning
confidence: 99%
“…These drugs show favourable antiviral activity in vitro. Moreover, some compounds, such as lemon essential oil, theaflavins-enriched tea leaf extract TY-1 and monogalactosyldiacylglyceride, exert virucidal effects [1,24,25]. Currently, few antiviral drugs are approved for the clinical treatment of FCV [26].…”
Section: Introductionmentioning
confidence: 99%